Fractional CO2 laser treatment for vaginal laxity: A preclinical study. Issue 9 (7th May 2018) - Kwon, Tae‐Rin; Kim, Jong Hwan; Seok, Joon; Kim, Jae Min; Bak, Dong‐Ho; Choi, Mi‐Ji; Mun, Seok Kyun; Kim, Chan Woong; Ahn, Seungwon; Kim, Beom Joon
Abstract : Background and Objective: Various studies have investigated treatment for vaginal laxity with microablative fractional carbon dioxide CO2 laser in humans; however, this treatment has not yet been studied in an animal model. Herein, we evaluate the therapeutic effects of fractional CO2 laser for tissue remodeling of vaginal mucosa using a porcine model, with the aim of improving vaginal laxity. Study Design/Materials and Methods: The fractional CO2 laser enables minimally invasive and non‐incisional procedures. By precisely controlling the laser energy pulses, energy is sent to the vaginal canal and the introitus area to induce thermal denaturation and contraction of collagen. We examined the effects of fractional CO2 laser on a porcine model via clinical observation and ultrasound measurement. Also, thermal lesions were histologically examined via hematoxylin–eosin staining, Masson's trichrome staining, and Elastica van Gieson staining and immunohistochemistry. Results: The three treatment groups, which were determined according to the amount of laser‐energy applied (60, 90, and 120 mJ), showed slight thermal denaturation in the vaginal mucosa, but no abnormal reactions, such as excessive hemorrhaging, vesicles, or erythema, were observed. Histologically, we also confirmed that the denatured lamina propria induced by fractional CO2 laser was dose‐dependently increased after laser treatment. The treatment groups also showed an increase in collagen and elastic fibers due to neocollagenesis and angiogenesis, and the vaginal walls became firmer and tighter because of increased capillary and vessel formation. Also, use of the fractional CO2 laser increased HSP (heat shock protein) 70 and collagen type I synthesis. Conclusion: Our results show that microablative fractional CO2 laser can produce remodeling of the vaginal connective tissue without causing damage to surrounding tissue, and the process of mucosa remodeling while under wound dressings enables collagen to increase and the vaginal wall to become thick and tightened. Lasers Surg. Med. 50:940–947, 2018. © 2018 Wiley Periodicals, Inc.